2007
DOI: 10.1016/j.pce.2007.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater harvesting to enhance water productivity of rainfed agriculture in the semi-arid Zimbabwe

Abstract: Zimbabwe's poor are predominantly located in the semi-arid regions (Bird and Shepherd, 2003) and rely on rainfed agriculture for their subsistence. Decline in productivity, scarcity of arable land, irrigation expansion limitations, erratic rainfall and frequent dry spells, among others cause food scarcity. The challenge faced by small-scale farmers is to enhance water productivity of rainfed agriculture by mitigating intra-seasonal dry spells (ISDS) through the adoption of new technologies such as rainwater ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 7 publications
2
32
0
1
Order By: Relevance
“…Previous studies have indicated that increasing rainwater harvest and conservation, improving water productivity and increasing plant water uptake capacity can mitigate water stress and optimize crop production (Kahinda et al 2007;Rockström and Barron 2007;Rockström et al 2010). In our study, the maize grain yields were significantly higher in the GM and FM treatments than in the CK treatment (Table 3).…”
Section: Discussionmentioning
confidence: 44%
“…Previous studies have indicated that increasing rainwater harvest and conservation, improving water productivity and increasing plant water uptake capacity can mitigate water stress and optimize crop production (Kahinda et al 2007;Rockström and Barron 2007;Rockström et al 2010). In our study, the maize grain yields were significantly higher in the GM and FM treatments than in the CK treatment (Table 3).…”
Section: Discussionmentioning
confidence: 44%
“…Although the results are very similar, Method 2 gives a slightly higher score for the jessour in Sub-catchment 2 (jessour 10-16) and Sub-catchment 3 (jessour [1][2][3][4][5][6][7][8].…”
Section: Comparison Of Methods 1 Andmentioning
confidence: 79%
“…RWH is a method for inducing, collecting, storing and conserving local surface runoff for agriculture in arid and semi-arid regions [2]. RWH is a likely viable option to increase water productivity at the production system level [3]. RWH and management techniques have a significant potential for improving and sustaining the rainfed agriculture in the region [4].…”
Section: Introductionmentioning
confidence: 99%
“…LID devices, such as rain barrels, have long been used for rainwater harvesting in many parts of the world where annual rainfall is moderate to abundant (Australia—Rodrigo, Sinclair, & Leder, ; Huston, Chan, Chapman, Gardner, & Shaw, ; Wang & Blackmore, ; Bangladesh—Karim, ; Brazil—Pacheco, Gomez, Oliveira, & Teixeira, ; Europe—Palla, Gnecco, Lanza, & La Barbera, ; Malaysia—Lee, Mokhtar, Hanafiah, Halim, & Badusah, ; Nigeria—Aladenola & Adeboye, ; Korea—Han & Mun, ; Italy—Liuzzo, Notaro, & Freni, ; United States—Keithley, ; Fricano & Grass, ) as well as in areas with semiarid to arid regions with low annual rainfall (Bakir & Liang, ; National Institute of Hydrology, ; Li, Gong, & Wei, ; Kahinda, Rockstrom, Taigbenu, & Dimes, ) and as an alternative source for potable and nonpotable water use (i.e., lawn irrigation, crop production; Imteaz, Adeboye, Rayburg, & Shanableh, ; Thomas, Kirisits, Lye, & Kinney, ; Boers & Ben‐Asher, ). This reduces water bills and saves energy used to produce and transport water, thus making it a viable strategy for supplementing local water supply both in areas with higher or lower risk of water scarcity (Dallman, Chaudhry, Muleta, & Lee, ; Ruberto, Lee, & Bayer, ).…”
Section: Introductionmentioning
confidence: 99%